ISOLATION, MENTAL HEALTH, BODY COMPOSITION OF PHYSICAL EDUCATION TEACHERS (Fiep Bulletin - online, 2025)
Introduction: The Covid-19 pandemic has been very harmful to different professions, especially teachers. Thus, when reviewing the relevant literature, gaps in knowledge were observed regarding the effect of the pandemic on teachers' health. Aim: To analyze the effect of social isolation during the Covid-19 pandemic on the mental health and body composition of Physical Education teachers in João Pessoa. Methods: This research is characterized as being descriptive, cross-sectional, and qualitative. The sample consisted of 114 Physical Education teachers from the city of João Pessoa, Paraíba. A questionnaire was applied to the teachers with questions that referred to the past (before the pandemic) and at the time they were (during the pandemic). The questions asked were about stress levels, health, body composition, and physical activity practice. The McNemar test was used for dichotomous qualitative data, and the Wilcoxon test was used for ordinal polytomous qualitative data. Results: In the comparative analysis of stress levels, health and body mass index classification by the Wilcoxon test, it was observed that there was a significant difference when comparing before and during the pandemic (p
Keywords: Teachers; Mental Health; Covid-19; Social Isolation